Pedagogical Compatibility Between Active Learning Approaches and Islamic Educational Values: A Conceptual Review - R Mhd Kadri; Fuji Arifzapni; Ravvi Yuhendri Saputra; Arwansyah Kirin (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine the concepts, characteristics, advantages, and relevance of implementing active learning, cooperative learning, and collaborative learning from the perspective of Islamic education. It focuses on analyzing the compatibility between group-based active learning approaches and Islamic values such as consultation (shura), mutual assistance, responsibility, and brotherhood. This research employs a library research method with a qualitative descriptive approach. Data were collected from scientific journal articles, academic books, and normative Islamic sources, including the Qur’an, Hadith, and classical and contemporary scholars’ works. Data were analyzed using content analysis by examining and synthesizing key ideas from the sources. The findings indicate that cooperative and collaborative learning enhance student engagement, develop social skills, and shape character. These approaches are consistent with Islamic educational principles emphasizing togetherness, justice, and collective responsibility. Thus, group-based active learning is pedagogically, morally, and spiritually relevant in Islamic education.